MENINGKATKAN MOTORIK HALUS ANAK MELALUI MEDIA KOLASE PADA USIA 5-6 TAHUN DI PAUD MUTIARA KASIH TAHUN PELAJARAN 2020-2021 - Perenika; Saripah; Asyruni Multahada (Lunggi Journal, 2026)
The purpose of this study is to reveal:1) the teacher’s goals in improving the fine motor skills of early childhoon though collage media at Muara Kasih PAUD, Semata Village, 2020-2021 academic year. 2) the teacher’s method in improving the fine motor skills of children aged 5-6 years through collage media at mutiara kasih PAUD, Semata Village 2020-2021 academic years This research uses a qualitative approach which uses data collection research methods using interview, observation, and documentation techning, while data analysis techniques use data reduction or selection, data display or presentation, and conclusions. The results of the study indicate that: The teacher’s goals in improving fine motor skills in early childhood through collage media at Muara Kasih Early Childhood education (PAUD) in Semata Village are: a) the abikity to function small muscles such as finger movements, b) the ability to coordinate hand and eye speed, c) the ability to control emotions. The teacher’s steps in improving fine motor skills in early childhood though collage media at Mutiara Kasih Early childhood though education (PAUD) in Semata Village in 2020-2021 are: a) preparinf or planning the image to be created, b) providing the materials and tools to be used for the collage media activity, d) guiding children to applying adhesive using sufficient glue, e) explaining the correct position for attaching the image pattern according to the shape of the image, and the teacher assessing the students’ work. F) the teacher assesses the children’s work.